2020
DOI: 10.46497/archrheumatol.2020.7583
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interstitial Lung Disease With Clinical Characteristics of Chinese Patients With Systemic Lupus Erythematosus

Abstract: Objectives: This study aims to evaluate the frequency and clinical and laboratory features of interstitial lung disease (ILD) in Chinese patients with systemic lupus erythematosus (SLE) and to evaluate the association of ILD with the clinical features. Patients and methods: The study included 505 SLE patients (64 males, 441 females; mean age 35.3±15.3 years; range, 14 to 87 years) who were categorized into two groups as 449 patients without ILD and 56 patients with ILD based on evidence obtained from high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…On the other hand, a previous necropsy study identified pulmonary fibrosis in only four lung specimen from 120 SLE patients 5 . Consistent with the literature, ILD in SLE was related to age and other comorbid conditions 11,12 …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…On the other hand, a previous necropsy study identified pulmonary fibrosis in only four lung specimen from 120 SLE patients 5 . Consistent with the literature, ILD in SLE was related to age and other comorbid conditions 11,12 …”
Section: Discussionsupporting
confidence: 82%
“…5 Consistent with the literature, ILD in SLE was related to age and other comorbid conditions. 11,12 Indeed, almost a third of SLE patients with ILD had, in addition to SLE, another autoimmune disorder-such as Sjögren's syndrome, systemic sclerosis, mixed connective tissue disorder or inflammatory myopathy-which all are at specific risk for lung involvement. The frequency of ILD in SLE is thus exceedingly rare and a high proportion of SLE patients with ILD had an 'overlapping' SLE.…”
Section: Discussionmentioning
confidence: 99%
“…People with SLE, a condition associated with a dramatic gender disparity in adults (9:1, female:male), have many reported pulmonary complications including pleural disease, ILD, vasculitis, pulmonary embolism, pulmonary hypertension, large airway disease, shrinking lung syndrome, and infection. Historically, the prevalence of SLE-associated ILD has been suggested to be very low, between 3 and 9% [ 76 , 77 ] although these figures predate high resolution CT. More recent estimates show the prevalence closer to 10% [ 78 ] with maintenance of the female predominance seen in adult SLE. Major risk factors for developing SLE-associated ILD include long disease duration, and in particular older age at onset.…”
Section: Connective Tissue Diseasesmentioning
confidence: 97%
“…Chronic interstitial lung disease (ILD) in SLE seems to be less frequent in comparison to other connective tissue diseases (CTDs), and it is rarely severe [ 10 , 48 , 49 , 50 ]. The exact prevalence is probably underestimated, because older studies performing chest X-ray have shown the presence of ILD in 6–24% of SLE patients, while in those using a more sensitive method such as HRCT, ILD was found in up to 70% of cases, suggesting that the condition is frequently subclinical [ 10 , 49 , 51 ].…”
Section: Parenchymal Lung Diseasementioning
confidence: 99%
“…The exact prevalence is probably underestimated, because older studies performing chest X-ray have shown the presence of ILD in 6–24% of SLE patients, while in those using a more sensitive method such as HRCT, ILD was found in up to 70% of cases, suggesting that the condition is frequently subclinical [ 10 , 49 , 51 ]. Risk factors for ILD include older age, late-onset SLE, illness duration (≥1 year), tachypnea, low levels of anti-dsDNA, high level of C3 and male gender [ 48 , 49 , 50 , 51 , 52 ]. The presence of Raynaud’s phenomenon, swollen fingers, sclerodactyly, telangiectasia, nailfold capillary abnormalities among SLE patients was associated with a higher prevalence of restrictive deficit and reduced DLCO, probably in the context of overlap syndromes that seem to carry a worse lung prognosis.…”
Section: Parenchymal Lung Diseasementioning
confidence: 99%